Manuscript of broadcast on KRTN Radio - Hayden, Jack (Raton, NM, 1950)
This was broadcast of KRTN Radio. The text covers the writer's approval of the El Portal Hotel (sponsor of program), and some family history as well as boyhood memories. The writer/speaker was the cousin of Evlyn Shuler. son of Dr. and Mrs. Hayden, Great Aunt Pamela Letton, her descendents Mrs. Pearl Kellog, Mrs. Anita Kiser, and Marion Sinnock.
Article written by local people
Master list item #: 10
In text: ". . .a historical program sponsored by the El Portal Hotel."
File location is in the Raton File Cabinet
2 Copies
Keywords: Narrator Jack Hayden; Shuler, Evlyn; Gearhardt, (Mr.); Gearhardt, (Mrs.); Budd, Anna Ray; Hayden, Mary Kathryn; Seeberg, Agnes; Seeberg, (Mr.); Lettom, Pamela; Kellog, Pearl; Kiser, Anita; Sinnock, Marion; Long, Emily; Letton, Rube; El Portal; Van Buskirk Ranch; Seeberg Hotel; Old Sandusky house; Santa Fe Railroad; Whistler's ranch; History -- Raton, New Mexico; Local History; Life and Customs; Upstanding file material. -- Located in upstanding file "Raton - History - Articles by Local People"